2016
DOI: 10.1111/tbj.12595
|View full text |Cite
|
Sign up to set email alerts
|

Management of Early Node-Positive Breast Cancer in Australia: A Multicentre Study

Abstract: To examine practice patterns for breast cancer patients with limited sentinel node (SN) disease in light of the ACOSOG Z0011 results. Retrospective analysis of patients with T1-2 breast cancer and positive sentinel lymph node biopsy (SLNB) admitted between January 2009 and December 2012. Patient demographics, tumor characteristics, and treatments were recorded. Eight hundred positive SLNBs were identified. A total of 452 (56.5%) proceeded to completion axillary lymph node dissection (cALND). cALND rate decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In studies initiated by Giuliano et al, it has been established that regardless of SLN lesions, it is possible to refrain from ALND in selected breast cancer patients. These studies were followed by analyses reported by other authors, including one study conducted at our department . The collecting of further clinical evidence validating such a decision can substantiate the general application of conservative treatment (similarly to SLN(+) patients with micrometastases).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In studies initiated by Giuliano et al, it has been established that regardless of SLN lesions, it is possible to refrain from ALND in selected breast cancer patients. These studies were followed by analyses reported by other authors, including one study conducted at our department . The collecting of further clinical evidence validating such a decision can substantiate the general application of conservative treatment (similarly to SLN(+) patients with micrometastases).…”
Section: Discussionmentioning
confidence: 97%
“…In the years 2009 and 2010 (pre‐Z0011 era), 16.9% of our patients qualified for observation. However, in the years 2011 and 2012 (post‐Z0011 era), the percentage reached 31.2% …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is in part due to the initial reservations by many Australian surgeons and oncologists regarding the Z0011 study methodology such as the trial closing early with less than 50% target accrual, high survival and low event rate, significant number of women lost to follow‐up, and the radiation techniques not clearly described such as dosing, frequency and field definitions. The ongoing UK‐ANZ POSNOC trial will include 1900 women with around 250 women from Australia and New Zealand. This multicenter non‐inferiority prospective randomized trial aims to assess whether adjuvant therapy alone is no worse than adjuvant therapy plus axillary treatment for early breast cancer with one or two sentinel nodes containing macrometastases.…”
Section: Discussionmentioning
confidence: 99%